Radiation properties of metamaterials in millimeter wavelength region; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Shevelev M. V. Mihail Viktorovich; Soboleva V. V. Veronika Vyacheslavovna; Bleko V. V. Vitold Vladislavovich (2012, 2012)
Title screen